Long-Term Clinical Outcomes in Patients With an Acute ST-Segment-Elevation Myocardial Infarction Stratified by Angiography-Derived Index of Microcirculatory Resistance - Kotronias, Rafail A.; Terentes-Printzios, Dimitrios; Shanmuganathan, Mayooran; Marin, Federico; Scarsini, Roberto; Bradley-Watson, James; Langrish, Jeremy P.; Lucking, Andrew J.; Choudhury, Robin; Kharbanda, Rajesh K.; Garcia-Garcia, Hector M.; Channon, Keith M.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aims: Despite the prognostic value of coronary microvascular dysfunction (CMD) in patients with ST-segment-elevation myocardial infarction (STEMI), its assessment with pressure-wire-based methods remains limited due to cost, technical and procedural complexities. The non-hyperaemic angiography-derived index of microcirculatory resistance (NH IMRangio) has been shown to reliably predict microvascular injury in patients with STEMI. We investigated the prognostic potential of NH IMRangio as a pressure-wire and adenosine-free tool. Methods and Results: NH IMRangio was retrospectively derived on the infarct-related artery at completion of primary percutaneous coronary intervention (pPCI) in 262 prospectively recruited STEMI patients. Invasive pressure-wire-based assessment of the index of microcirculatory resistance (IMR) was performed. The combination of all-cause mortality, resuscitated cardiac arrest and new heart failure was the primary endpoint. NH IMRangio showed good diagnostic performance in identifying CMD (IMR > 40U); AUC 0.78 (95%CI: 0.72–0.84, p < 0.0001) with an optimal cut-off at 43U. The primary endpoint occurred in 38 (16%) patients at a median follow-up of 4.2 (2.0–6.5) years. On survival analysis, NH IMRangio > 43U (log-rank test, p < 0.001) was equivalent to an IMR > 40U(log-rank test, p = 0.02) in predicting the primary endpoint (hazard ratio comparison p = 0.91). NH IMRangio > 43U was an independent predictor of the primary endpoint (adjusted HR 2.13, 95% CI: 1.01–4.48, p = 0.047). Conclusion: NH IMRangio is prognostically equivalent to invasively measured IMR and can be a feasible alternative to IMR for risk stratification in patients presenting with STEMI.